Mechanical properties of geopolymers reinforced with carbon and aramid long fibers. (November 2019) - Łach, M; Hebdowska-Krupa, M; Mierzwiński, Dariusz; Korniejenko, Kinga
Abstract: The paper presents the results of the study of geopolymer composites reinforced with carbon and aramid fibers. Geopolymers were made on the basis of fly ash activated with 10 mole sodium hydroxide solution with an addition of aqueous sodium silicate solution. The fibers were introduced in the form of a roving. Carbon fibers 800 tex and aramid fibers 805 tex were used. Additionally, to compare the influence of the number of fibers on the properties of geopolymer composites for carbon fiber, 1600 tex fiber was also used. The flexural strength of composites made with the fibers was tested. Fiber reinforced geopolymer composites showed a higher value of flexural strength than unreinforced ones. The higher value was noted for carbon fiber reinforced composites (800 tex) compared to aramid fiber roving composites (805 tex). The study also showed that the application of higher fiber mass in the case of carbon fiber roving does not bring the expected increase in mechanical properties of the composites. The use of carbon fiber roving (1600 tex) resulted in a lower flexural strength than in the case of 800 tex roving. Double increase of fiber mass in the composite caused a decrease in strength parameters.